Analisis Pengaruh Investasi Dan Jumlah Industri Terhadap Penyerapan Tenaga Kerja Pada Sektor Industri Kecil Dan Menengah Di Kabupaten Lombok Timur - Kholiani, Nofita; Yudha Senopati, I Dewa Ketut (Universitas Mataram, 2024)
The population growth in East Lombok Regency continues to increase, requiring adequate job opportunities to reduce unemployment and poverty. Employment absorption in the small and medium industries sector is expected to be a solution. This study aims to analyze the impact of investment and the number of industries on employment absorption, both partially and simultaneously. The research adopts a descriptive quantitative approach using multiple linear regression analysis. The results show that both variables have a positive and significant partial effect on employment absorption. Investment has a t-value of 2.748 > 2.306 t-table, while the number of industries has a t-value of 2.866 > 2.306 t-table. Simultaneously, the independent variables significantly influence employment absorption. The R² value of 79.2% indicates that the independent variables explain the dependent variable, while the remaining 20.8% is influenced by factors outside the model. These findings highlight the importance of investment and industrial development in increasing employment opportunities in East Lombok Regency.